Root dentin anomaly and a PLG mutation - Napaporn Tananuvat (2018)
© 2014 Elsevier Masson SAS. We report a Thai girl affected with plasminogen deficiency, Type I. Ligneous conjunctivitis was first observed when she was one-month-old. The newly recognized findings include tapered incisor roots as a result of thin root dentin, generalized short tooth roots, and mandibular prognathism. Mutation analysis of PLG demonstrated homozygous c.1193G>A missense mutation. The parents were heterozygous for c.1193G>A mutation. The c.1193G>A mutation is novel and predicted to cause amino acid substitution p.Cys398Tyr. Thin root dentin in the patient who was affected with PLG mutation and immunolocalization of Plg during early root development in mice imply the role of plasminogen in root dentin formation.